A novel ultrasound-driven piezoelectric GBR membrane dispersed with boron nitride nanotubes promotes bone regeneration and anti-bacterial properties - Keshi Zhu; Ruixue Li; Shi Yin; Fei Yang; Yang Sun; Yixiao Xing; Yiling Yang; Wanjing Xu; Youcheng Yu (Materials Today Bio)
Bone graft absorption and infection are the major challenges to guided bone regeneration(GBR), yet the GBR membrane is neither osteogenic nor antibacterial. Hence, we followed sono-piezo therapy strategy by fabricating an electrospun membrane dispersed with boron nitride nanotubes. The PLLA/Gelatine/PDA@BNNT (PGBT) membrane has improved mechanical and biocompatible properties and generate piezovoltages of 130 mV when activated by ultrasound stimulation under 100 mW/cm2 without extra polarization. The PGBT with ultrasound is conducive to cellular osteogenesis, barrier function, and shows antibacterial rate of about 40 %. The rat cranial defect experiments revealed that PGBT with ultrasound could promote osteogenesis in-vivo and show great potentials for vertical bone defect repair.